A resisted sprint improves rate of force development during a 20-m sprint in athletes - Mangine, G. T.; Huet, K.; Williamson, C.; Bechke, E.; Serafini, P.; Bender, D.; Hudy, J.; Townsend, J. (The Journal of Strength and Conditioning Research, 2018)
This study examined the effect of a resisted sprint on 20-m sprinting kinetics. After a standardized warm-up, 23 (male = 10, female = 13) Division I basketball players completed 3 maximal 20-m sprint trials while tethered to a robotic resistance device. The first sprint (S1) used the minimal, necessary resistance (1 kg) to detect peak (PK) and average (AVG) sprinting power (P), velocity (V), and force (F); peak rate of force production (RFD) was also calculated. The second sprint (S2) was completed against a load equal to approximately 5% of the athlete's body mass. Minimal resistance (1 kg) was again used for the final sprint (S3). Approximately 4-9 minutes of rest was allotted between each sprint. Separate analyses of variance with repeated measures revealed significant (p = 0.05) main effects for all sprinting kinetic measures except VPK (p = 0.067). Compared with S1, increased (p < 0.006) 20-m sprint time (3.4 ± 4.9%), PAVG (115.9 ± 33.2%), PPK (65.7 ± 23.7%), FAVG (134.1 ± 34.5%), FPK (65.3 ± 16.2%), and RFD (71.8 ± 22.2%) along with decreased (p < 0.001) stride length (-21 ± 15.3%) and VAVG (-6.6 ± 4.6%) were observed during S2. During S3, only RFD was improved (5.2 ± 7.1%, p < 0.001) compared with S1. In conclusion, completing a short, resisted sprint with a load equating to 5% of body mass before a short sprint (~20-meters) does not seem to affect sprinting time or kinetics. However, it does appear to enhance RFD.